Sistem Pendukung Keputusan Perekrutan Karyawan Online Untuk Penerimaan Karyawan Dengan Metode MOORA - Fatmawati, F; Handayanna, Frisma; Purnamasari, Indah (STIKOM Tunas Bangsa Pematangsiantar, 2020)
One company that always gets a lot of prospective employees is PT. Fullmoon Jaya Abadi is engaged in the wholesale trade of special CCTV material. At PT. Fullmoon Jaya Abadi data obtained from the employee recruitment process still use manual methods, so the HRD (Human Resource Development) division must sort and select applicants one by one. A large number of candidates make the HRD division often have difficulty in choosing prospective employees, and subjectivity occurs when they want to decide so that the company accepts employees who do not fit the criteria set by the company. To overcome the problem of making decisions on employee acceptance at PT. Jaya Fullmoon Abadi is using the Multi-Objective Optimization method based on ratio analysis (MOORA). In research data collected based on the position of prospective employees. The results obtained in this study determine each position to receive as many as three prospective employees, namely Arianto Wibowo, Deny Saputra, and Irdha Febriani Awaliyah Ibrahim in the Sales position. Ilham Akbar N.S, Johan Salim, and Alfi Muhayyar in the Graphic Design position. Agustin Sulistyani, Sri Mulyani, and Serli Damayanti in the Accounting Staff position. Hendri Tanu, Adinda Helena, and Wajum Rodi in the IT Support position. Hartopo and Taufik Hidayat in the position of Sales Project.